Predictive factors of neoplastic gallbladder polyps: Outcomes of 278 patients - Terzioğlu, Serdar Gökay; Kılıç, Murat Özgür; Sapmaz, Ali; Karaca, Ahmet Serdar (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Distinguishing between neoplastic and nonneoplastic gallbladder polyps (GBPs) in the preoperative workup is of great importance for appropriate treatment. The present study aimed to investigate the characteristics of GBPs and to determine potential predictive factors of neoplastic polyps. Materials and Methods: The data of 278 patients who were confirmed to have GBPs through laparoscopic cholecystectomy were retrospectively analyzed. Polyps were classified as nonneoplastic and neoplastic GBPs, according to histopathological diagnoses. All clinicopathological characteristics were compared between these two groups. Results: There were 264 (95%) nonneoplastic GBPs and 14 (5%) neoplastic GBPs. In univariate analysis, there were significant differences in age with a cutoff value of 60 years (p=0.002), polyp size (p<0.001), number of polyps (p=0.014), and polyp morphology (p<0.001) between the groups. Multivariate analysis showed that solitary polyp (p<0.001) and sessile morphology (p<0.001) were the independent predictors of neoplastic GBPs. Receiver-operating characteristic curve analysis of three cut-off values of polyp sizes (6, 10, and 15 mm) indicated that a polyp size of 10 mm had the highest area under curve (0.942). Conclusion: Age above 60 years, solitary polyps larger than 1 cm, and sessile morphology are associated with an increased risk of neoplasia in GBP. Therefore, these characteristics should be considered in the management of GBPs to reduce the incidence of unnecessary surgeries and to prevent delays in the treatment of a possible cancer.